On the existence of initial values of solutions of weakly nonlinear parabolic equations - Skrypnik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We study the properties of solutions of weakly nonlinear parabolic equations in cylindrical domains. The existence conditions are established for local nontangential limits as t → 0.